The Hadhrami diaspora in Southeast Asia : identity maintenance or assimilation? - Abushouk, Ahmed Ibrahim; Ibrahim, Hassan Ahmed (Social, economic, and political studies of the Middle East and Asia ;, 2009)
Based on the proceedings of an international conference convened by the Department of History and Civilisation, International Islamic University Malaysia, in collaboration with the Embassy of the Republic of Yemen in Kuala Lumpur, from 26th to 28th August 2005, this title reviews twelve out of thirty-five papers presented at the conference.